Physical Properties of Copper Based MMC Strengthened with Alumina - Kaczmar J. W.; Granat K.; Kurzawa A.; Grodzka E. (Archives of Foundry Engineering, 2014)
The aim of this work is the development of Cu-Al2O3 composites of copper Cu-ETP matrix composite materials reinforced by 20 and 30 vol.% Al2O3 particles and study of some chosen physical properties. Squeeze casting technique of porous compacts with liquid copper was applied at the pressure of 110 MPa. Introduction of alumina particles into copper matrix affected on the significant increase of hardness and in the case of Cu-30 vol. % of alumina particles to 128 HBW. Electrical resistivity was strongly affected by the ceramic alumina particles and addition of 20 vol. % of particles caused diminishing of electrical conductivity to 20 S/m (34.5% IACS). Thermal conductivity tests were performed applying two methods and it was ascertained that this parameter strongly depends on the ceramic particles content, diminishing it to 100 Wm-1K-1 for the composite material containing 30 vol.% of ceramic particles comparing to 400 Wm-1K-1 for the unreinforced copper. Microstructural analysis was carried out using SEM microscopy and indicates that Al2O3 particles are homogeneously distributed in the copper matrix. EDS analysis shows remains of silicon on the surface of ceramic particles after binding agent used during preparation of ceramic preforms.